2008
DOI: 10.1590/s1806-83242008000300002
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of a resin cement to dentin using the resin coating technique

Abstract: The aim of this study was to evaluate the bond strength of a resin cement to dentin using different adhesive systems (AS) in the presence or absence of a low-viscosity composite liner (Protect Liner F -PLF) applied over the bonded dentin. The adhesive systems selected were: AdheSE/Vivadent (AD); Clearfil Protect Bond/Kuraray (CP); One-Up Bond F/Tokuyama (OU); Single Bond/3M ESPE (SB); Tyrian SPE/One-Step Plus/Bisco (TY); Xeno III/Dentsply (XE) and Unifil Bond/GC (UN). After removing the labial and lingual enam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…The increase in bond strength of Panavia F 2.0 is in line with the result of previous works 3,5,6,25) . The conventional application of this resin cement with ED Primer II as bonding agent could not result in high bond strength values to dentin 16,21) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in bond strength of Panavia F 2.0 is in line with the result of previous works 3,5,6,25) . The conventional application of this resin cement with ED Primer II as bonding agent could not result in high bond strength values to dentin 16,21) .…”
Section: Discussionsupporting
confidence: 92%
“…The use of resin coating also facilitates the cementation process and reduces the postoperative sensibility, since the dentin sealing and hybridization are achieved immediately after cavity preparation [2][3][4] . The recommended procedure for resin coating consists of the application of a two-step self-etching bonding system and a low viscosity composite resin to dentin 5,6) . Impression taking and placement of the provisional restoration are performed while dentin surface is covered under the resin coating.…”
Section: Introductionmentioning
confidence: 99%
“…However, when Weilbull distribution is considered, both mechanical cleansing methods provided less reliable adhesion results as opposed to other methods based on air-abrasion. Similarly, Santos et al have reported negative effect of the use of pumice on the bond 11 strength of the resin to fresh dentin due to obscuration of the dentinal tubule openings by pumice residues [31]. Thus, the use of air-abrasion still seems to be more beneficial to optimize adhesion of resin cement to IDS.…”
Section: Discussionmentioning
confidence: 96%
“…HEMA is one of the main components used in dental restorative materials because of its relevant physico‐chemical and mechanical characteristic (Santos‐Daroz et al. 2008; Garcia et al.…”
Section: Discussionmentioning
confidence: 99%